INFLUENCE OF PROJECT RISK MANAGEMENT PRACTICES ON PERFORMANCE OF TELECOMMUNICATION NETWORK MODERNISATION PROJECTS IN KENYA - Maritim, Samuel Kipkoech; Chelule, Dr. Kenneth (European Journal of Business and Strategic Management, 2018)
Purpose: Telecommunication operators around the world continue to upgrade their network technologies to improve performance and increase capacity. Many of these firms are confronted with the challenge of ensuring successful implementation of these projects. The general objective of this study was to establish the influence of project risk management practices on performance of Telecommunication Network Modernization projects in Kenya. Methodology: This study adopted a case study research design. The target population for the study was Network Modernization projects undertaken by Safaricom Plc in the past three years. The unit of observation were the Project Managers and Technical Team leaders who are responsible for the management of the selected Network modernization projects. A total of sixty Network modernization projects were selected. Total number of 60 respondents was reached, representing the entire population. Census was used in the study. Primary data was collected using semi-structured questionnaire based on the objectives of the study. The data was edited, coded for processing using the Statistical Package for Social Sciences (SPSS v.24) and presented in tabular and graphical format. A master codebook designed to ensure that all the questionnaires are coded uniformly was used. Consequently, data was edited for completeness and consistency before analysis. The study used multiple regression analysis and Analysis of Variance (ANOVA) to analyze the degree of relationship between the variables in the study at 5% level of significance. Results: The study found that all the four aspects of risk management were practiced to a high extent. Regression analysis yielded relationships between performance of network modernization projects against project risk identification, project risk monitoring and project risk response. Though these relationships were weak, they were found to be statistically significant at the 5% significance level. Project risk analysis was found to have no relationship with performance of network modernization projects. Unique contribution to Theory, Practice and Policy: The study recommended that telecommunication firms should pay great emphasis on the three aspects of risk management, namely project risk identification, project risk monitoring and project risk response. Further it was recommended that future studies should be done to establish other factors that influence performance of Telecomm Network Modernization projects.